2017
DOI: 10.1002/dvdy.24600
|View full text |Cite
|
Sign up to set email alerts
|

hace1 Influences zebrafish cardiac development via ROS‐dependent mechanisms

Abstract: Our study demonstrates that HACE1 is critical in the normal development and proper function of the vertebrate heart via a ROS-dependent mechanism. Developmental Dynamics 247:289-303, 2018. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…ROS participate in the development of the nervous system, the differentiation and formation of the nerve, and the development of lung and vascular tissue [38]. Recently, an article reported that high levels of ROS lead to heart looping disorder during heart development [39,40]. There are also Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ROS participate in the development of the nervous system, the differentiation and formation of the nerve, and the development of lung and vascular tissue [38]. Recently, an article reported that high levels of ROS lead to heart looping disorder during heart development [39,40]. There are also Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus they suggest that phenotypes in xenopus could be linked to the maternal pool of RNA. Recently, a study demonstrated that HACE1 is involved in the normal development and proper function of the heart in zebrafish [77]. However, authors used splice-site morpholinos suggesting that this cardiac phenotype could be due to later zygotic expression of HACE1.…”
Section: Discussionmentioning
confidence: 99%
“…It participated in the development of the nervous system, promoting the differentiation and the formation of the nerve, and the development of lung and vascular (32). Recently, an article reported that high levels of ROS lead to heart looping disorder during heart development (33,34). There were also many reports that environmental poisons and drugs such as doxorubicin (35) and chlorpyrifos(36) caused abnormal development of various organs by inducing ROS accumulation.…”
Section: Discussionmentioning
confidence: 99%